CITRA GERAKAN POLITIK ISLAM DALAM LINTASAN SEJARAH PERPOLITIKAN BANGSA INDONESIA (Studi Era Pra Kemerdekan sampai dengan Era Orde Baru) - Kamsi Kamsi (Millah: Journal of Religious Studies, 2013)
In the pre-independence era and towards independence era of Indonesia, muslims become a political force that taken into account, it means muslims have an authority to make a decision that influence the future of Indonesia. The position of muslim was continoued until the birth of the Old Order. In the era of the Old Order or Democracy Guided, about relationship between muslims and the state at the time, the Muslims devided into two groups of politicalpatterns, first ijtihad,it is better for muslims to get into the system for the sake of Islam, while second ijtihadrecommended that muslims must fight the systemfor the sake of Islam. In the era of the New Order, the relationship between muslim and state was very unique, which was cordial in beginning, conflicting for long time, and finally going into intimate at the end of the era.